The insulin sensitiser metformin regulates chicken Sertoli and germ cell populations. Issue 5 (May 2016) - Faure, M; Guibert, E; Alves, S; Pain, B; Ramé, C; Dupont, J; Brillard, J P; Froment, P
Abstract: Metformin, an insulin sensitiser from the biguanide family of molecules, is used for the treatment of insulin resistance in type 2 diabetes individuals. It increases peripheral glucose uptake and may reduce food intake. Based on the tight link between metabolism and fertility, we investigated the role of metformin on testicular function using in vitro culture of Sertoli cells and seminiferous tubules, complemented by in vivo data obtained following metformin administration to prepubertal chickens. In vitro, metformin treatment reduced Sertoli cell proliferation without inducing apoptosis and morphological changes. The metabolism of Sertoli cells was affected because lactate secretion by Sertoli cells increased approximately twofold and intracellular free ATP was negatively impacted. Two important pathways regulating proliferation and metabolism in Sertoli cells were assayed. Metformin exposure was not associated with an increased phosphorylation of AKT or ERK. There was a 90% reduction in the proportion of proliferating germ cells after a 96-h exposure of seminiferous tubule cultures to metformin. In vivo, 6-week-old chickens treated with metformin for 3 weeks exhibited reduced testicular weight and a 50% decrease in testosterone levels. The expression of a marker of undifferentiated germ cells was unchanged in contrast to the decrease in expression of 'protamine', a marker of differentiated germ cells. In conclusion, these results suggest that metformin affects the testicular energy content and the proliferative ability of Sertoli and germ cells. Reproduction (2016) 151 527–538